PELAKSANAAN PEMBERIAN GANTI RUGI KEPADA PEMEGANG HAK ATAS TANAH DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM (STUDI KASUS PUTUSAN KONSINYASI NO.13/ PDT.P/KONS/2017/PN.PBR) - Ahsanu Ilham; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Infrastructure development in this case the highway itself is still very much needed asa means of supporting land transportation to help the economy in the community. Theincreasing volume of commercial land transportation vehicles (motorbikes, cars), publictransportation (buses, minibuses) and freight transportation (trucks) certainly requires alot of land / land so that there is no overcrowding of vehicles, especially during peak hoursthat occur sustainably. In carrying out this infrastructure development, parties who needland can use the other party's land rights by seeking approval from the land rights holder.Parties who need land can be pursued through the transfer of rights in the form of buyingand selling, or the release of land rights by the holder by providing compensation by theparties who need the land to the holder of the land rights. To anticipate land disputes andconflicts that will occur, legal tools and a neat and orderly land administration system areneeded, so as to guarantee and be able to provide legal protection to land rights ownersand can regulate the ownership, transfer and allotment of land in a fair andcomprehensive manner.Research using a type of Empirical Juridical research or Legal Sociology research isan approach used to see something legal reality in society. The Sociology of Law approachis an approach used to look at legal aspects in social interaction in society and serves as asupport for identifying and clarifying findings of non-legal materials for the purposes oflegal research or writing.From the results of the first study, the implementation of the provision ofcompensation to land rights holders based on convoluted Consignment Decisions cannotbe proven due to misunderstandings starting from the preparation stage, implementation,to submission of results and the implementation of the compensation process has beencarried out in accordance with laws and regulations. The lack of public understanding andthe laws governing the reference point of land assessment make this compensation processtime-consuming and do not show transparency of justice in question. Secondly, Theimplementation of compensation is hampered because there are parties who refuse theamount of compensation offered by the land acquisition implementation team with theresults of calculations from an independent. There is a discrepancy between the name ofthe previous land title holder and the current land owner, and the constraints of finding theowner of the land because the owner who has died or has also moved his domicile makesthe provision of compensation entrusted in court (consignment)Keywords: Consignment - Land Acquisition - Land Rights - Compansation